2018
DOI: 10.1002/jcc.25753
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the hydrogen bond in the crystals of tropolone and thiotropolone via car‐parrinello and path integral molecular dynamics

Abstract: Car‐Parrinello and path integrals molecular dynamics (CPMD and PIMD) simulations were carried out for the 10π‐electron aromatic systems: 2‐hydroxy‐2,4,6‐cycloheptatrien‐1‐one, commonly known as Tropolone (I) and 2‐hydroxy‐2,4,6‐cycloheptatriene‐1‐thione, called Thiotropolone (II) in vacuo and in the solid state. The extremely fast proton transfer (FPT) and “prototropy” tautomerism in the keto‐enol (thione‐enethiol) systems have been analyzed on the basis of CPMD and PIMD methods level. Comparisons of two‐dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 108 publications
(228 reference statements)
0
5
0
Order By: Relevance
“…Doering and Detert established the first rule of aromaticity in 1951‐the (4n+2) rule. This rule states that a cycloene with (4n+2) π electrons (where n is an integer) is aromatic [6] . The aromatic system is a circular closed conjugated system, [7,8] π electron is highly delocalized, has delocalization energy, system energy is low, relatively stable [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doering and Detert established the first rule of aromaticity in 1951‐the (4n+2) rule. This rule states that a cycloene with (4n+2) π electrons (where n is an integer) is aromatic [6] . The aromatic system is a circular closed conjugated system, [7,8] π electron is highly delocalized, has delocalization energy, system energy is low, relatively stable [9] .…”
Section: Introductionmentioning
confidence: 99%
“…This rule states that a cycloene with (4n + 2) π electrons (where n is an integer) is aromatic. [6] The aromatic system is a circular closed conjugated system, [7,8] π electron is highly delocalized, has delocalization energy, system energy is low, relatively stable. [9] Aromaticity cannot be directly measured by any physical or chemical experiment.…”
Section: Introductionmentioning
confidence: 99%
“…We used MC_MO methods to successfully evaluate the effects of NQEs and H/D isotopes in different hydrogen-bonded systems and proton transfer reactions. PIMD can also consider NQEs statistically within the Born–Oppenheimer approximation framework. , The PIMD approach considers NQEs as well as thermal effects. Many PIMD studies have been used to understand NQEs in the context of hydrogen-bonded systems, including LBHBs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides our study, only a few additional investigations have been reported, most of them using theoretical approaches. These studies have predicted the thione-enol tautomeric form of TT as being predominant in the gas phase as well as in aqueous solution and the solid state . However, there is still a lack of experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have predicted the thione-enol tautomeric form of TT as being predominant in the gas phase 48 as well as in aqueous solution 48 and the solid state. 49 However, there is still a lack of experimental data. The most relevant previously reported experimental results refer to the compound in solution and in the solid state, where Machiguchi et al claimed that TT exists as two rapidly equilibrating tautomeric (thione-enol and thiol-keto) structures.…”
Section: Introductionmentioning
confidence: 99%